Infertility of women in focus: risk factors and predictive outcome among women diagnosed with PCOS of Bangladesh - Chowdhury, Fahmida; Choden, Tshering (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.